Efektifitas Peran Assisten Sekretariat Daerah dalam Melaksanakan Tugas Pokok dan Fungsi Perangkat Sekretariat Daerah Kota Palangka Raya - Nanda Anisya Asmardiana; Novita Angraeni; Noval Firzatullah; Ulfa Syahida Rizkiya; Erza Nazhmi; M. Zaki Ramadhani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to determine the role of the Assistant Regional Secretariat of Palangka Raya City is very important in improving the performance of the Regional Secretariat apparatus in order to realize efficient and effective governance. This discussion highlights various aspects that influence the effectiveness of the role of the Assistant Regional Secretariat, such as coordination between regional apparatuses, human resource management (HR), budget management, performance monitoring, and employee motivation. Good coordination between regional apparatuses will facilitate the administration of government. In addition, competent HR management and efficient budget management are important factors in supporting the implementation of regional government programs. Performance monitoring and evaluation are also needed to ensure that every task and function of the Regional Secretariat apparatus runs according to plan. By considering all these factors, it is hoped that the performance of the Regional Secretariat apparatus can be more optimal and improve the quality of public services and regional government as a whole.